Optimising Ergonomic Risk Assessment Using Accelerometers in a 4D Environment - Medved, Tilen; Balantič, Zvone; Jarc Kovačič, Branka (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Reliable ergonomic risk assessment is the key to improving employee health and safety and reducing absenteeism. Today's innovative approaches to ergonomic assessment link the physical, biological and technological environment. The Movella Xsens wireless motion trackers (accelerometers – inertial sensors), which are attached to people, capture all movements in 3D space in real time and also reliably record the temporal dynamics of the positions of the body segments (4D environment). The computer tool from Siemens, Tecnomatix Process Simulate Human, is used to model the various morphological characteristics of employees and to design the workspace. The motion tracking sensors in the 4D environment have enabled more accurate measurements and therefore a more objective assessment of ergonomic risks. Consistent data collection enables fast and efficient ergonomic assessment. It enables faster and more efficient adaptation of workstations and rapid improvement of working conditions. A high level of responsiveness and rapid intervention in employee productivity and satisfaction are possible. In the long term, musculoskeletal disorders would be significantly reduced and the contribution to a more sustainable and healthier way of working significantly increased.